112k views
5 votes
Factor 2x^2 + 13x - 7

1 Answer

5 votes

Given the expression:


2x^2+13x-7

if we multiply it by 2/2, we get the following:


((2)/(2))(2x^2+13x-7)=(4x^2+26x-14)/(2)

which we can write in the following way:


(4x^2+26x-14)/(2)=((2x)^2+13(2x)-14)/(2)

then, we can factor the numerator using 2x as a variable. Then, we have the following:


((2x)^2+13(2x)-14)/(2)=((2x-1)(2x+14))/(2)

since the right factor has coefficients that are multiples of 2, we have:


((2x-1)(2x+14))/(2)=((2x-1)(x+7)(2))/(2)=(2x-1)(x+7)

therefore, the final factorization is (2x-1)(x+7)

User KTC
by
5.3k points